Pseudosperma arenarium (Inocybaceae), a new poisonous species from Eurasia, based on morphological, ecological, molecular and biochemical evidence - Yan Ya-Ya; Zhang Yi-Zhe; Vauras Jukka; Zhao Li-Na; Fan Yu-Guang; Li Hai-Jiao; Xu Fei (PENSOFT PUBLISHERS, 2022)
In this study, Pseudosperma arenarium is proposed as a new species, based on morphological, ecological, molecular and biochemical evidence. The new species grows on sandy ground under Populus and Pinus sylvestris in north-western China and northern Europe, respectively. It is characterised by the combination of the robust habit, nearly glabrous pileus, large cylindrical basidiospores, thin-walled cheilocystidia and eco-logical associations with Populus alba x P. berolinensis and Pinus sylvestris and unique phylogenetic place-ment. Additionally, a comprehensive toxin determination of the new species using ultra-high performance liquid chromatography-tandem mass spectrometry was conducted. Results showed that it was a mus-carine-positive species. The content were approximately five times higher in the pilei [4012.2 +/- 803.1- 4302.3 +/- 863.2 mg/kg (k = 2, p = 95%)] than in the stipes [850.4 +/- 171.1-929.1 +/- 184.2 mg/kg (k = 2, p = 95%)], demonstrating the severity of mushroom poisoning when patients consumed different parts of the poisonous mushroom. Amatoxins, phallotoxins, ibotenic acid, muscimol, psilocybin and psilocin were not detected.